ANTHROPOLOGICAL METHODS FOR DETERMINING A MAN'S CONSTITUTIONAL TYPE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The work presents the results of anthropometric examination of 605 men of the first period of maturity (21-35 years old), indicating the possibility of identifying the height, weight, and constitutional affiliation of unknown men by their remains.